“The poetic reason of María Zambrano opposite visions of Modern Humanism” - Briones Yela, Roberto Johann (2018)
María Zambrano sought ceaselessly - through his many writings - demonstrate that the reason not do without the innate transcendental dimension in human. This work, with the respective apologies to scholars in philosophy and the history of María Zambrano, presents the poetic reason as philosophical and pedagogical path to achieve transcendence. The greatest scholars of the world, is earned from these categories to find transcend. In our case, and not to get lost in the marshes of so many great ideologies, analyze the work of María Zambrano and his poetic reason proposing a humanistic paradigm shift, since the show philosophies pre-and humanists to intersperse the experiential philosophy of María Zambrano, to reach a philosophical attitude which prevails the thought to be, rather than to have.